Penjadwalan Kembali (Rescheduling) Tagihan Murabahah di Bank Rakyat Indonesia Syariah (BRIS) Kota Pekanbaru Berdasarkan Hukum Islam - Taufiqul Hulam; Muhammad Azani (Perspektif Hukum, 2016)
Rescheduling Murabaha bill on Islamic banking is suspected to add the amount of remaining bill that is unclearly allocated and categorized as usury. The research is a socio-legal study by using primary, secondary and tertiary data sources. The data are collected through observation, interview and documentation. The results of the research show that firstly, rescheduling the murabaha bill in Bank Rakyat Indonesia Syariah (BRIS), Pekanbaru City branch is to make a new contract of the rescheduling, while the previous contract is declared null and void. Secondly, in fact, BRIS Pekanbaru City branch does not fully apply the provision that the amount of Murabaha bill can not be increased. In practice, BRIS only calculates the amount of months that become the customer’s responsibility by reducing the amount of installments, and does not calculate the amount of Murabaha remaining bill before rescheduling. Thirdly, if the party does not fulfill his/her obligations or if there is a dispute between the parties, the dispute will be settled through mutual consultation, the National Sharia Arbitration Board and the Religious Courts. The parties can primarily conduct deliberations to solve the problems.